Effect of calcium and boron on biomass yield and nutrients uptake by tomato (Solanum lycopersicum) - Anil, Ajin S; Sharma, V K; Barman, Mandira; Datta, S P; Bandyopadhyay, K K; Singh, P K; Chobhe, Kapil A (The Indian Journal of Agricultural Sciences, 2020)
A pot experiment was conducted in acid soil (Alfisol) using four levels of lime (CaCO3) based on lime requirement (LR), viz. 0, 1/3, 2/3, and 1 and four levels of boron (B), viz. 0, 1.0, 1.5 and 2 mg/kg to evaluate the effect of applied calcium (Ca) and boron (B) on biomass yield, nutrient uptake of tomato (Solanum lycopersicum L.) and soil properties. The results indicated that application of Ca @ 2/3 LR and 1 LR significantly increased biomass yield of tomato by 21% and 16%, respectively over control. Boron application @ 1.0 mg/kg recorded highest biomass yield (19.6 g/pot) of tomato as compared to other boron treatments. Applied Ca @ 2/3 LR significantly increased the uptake of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulphur (S), zinc (Zn) and copper (Cu), whereas iron (Fe), manganese (Mn) and B uptake increased only up to Ca @ 1/3 LR treatment. Application of B increased the nutrients uptake over control, whereas it was observed significantly higher with B @ 1.5 mg/kg treatment. Applied Ca significantly enhanced the pH and available Ca in post-harvest soil, whereas salicylic acid extractable boron (SAE-B) was declined. The combined application of calcium @ 2/3 LR and B @ 1.5 mg/kg was most effective in enhancing the yield and nutrient uptake of tomato.